Analisis Penerapan MOORA dan WASPAS Dalam Pendukung Keputusan Penentuan Guru Komputer Terbaik - Mohammad Aldinugroho Abdullah; Rima Tamara Aldisa (STMIK Budi Darma, 2023)
A computer teacher is a teacher who provides a knowledge in which the knowledge leads to the field of computers. Teachers who master computer science are needed in every school because this knowledge is very difficult to understand if no one guides them. However, the more teachers in the computer field, the more difficult it is to know which teacher is the best with innovation and creativity in that field. So with that the writer needs 4 criteria in order to solve a problem that often occurs. These criteria include Education, Teaching Experience, Mastery of Computer Science, and Discipline. So in this research a helper system is really needed to solve the problems that occur in the research. The system referred to as an auxiliary tool in problem solving is the Decision Support System (DSS) which can be assisted in completing a calculation using the MOORA and WASPAS methods. So, in determining the best computer teacher using the MOORA method, Adian was chosen with a total score of 0.49347, while Adian was chosen with the WASPAS method with a total score of 1.00000.